Analisis Pengaruh PDB UMKM, Investasi UMKM, dan Upah Minimum Rata-Rata Nasional Terhadap Penyerapan Tenaga Kerja Sektor Umkm Indonesia Tahun 2006-2017 - Simanjuntak, Riama Dumaita; Sa’roni, Chairul (PPJP ULM, 2019)
The purpose of the research is to knoweffect of the gross domestic product of UMKM,the investment of UMKM, the minimum wage national average against the absorption oflabor in the UMKM sector, and the most dominant variable that affects the absorption ofwork in the UMKM sector. Tool analysis in this research is multiple linear regressionanalysis, and program application to analyzed data in this research is eviews version 9.The results showed the GDP of UMKM, Investment of UMKM, and the minimumwage national average simultaneously significantly affected the absorption of labor in theUMKM sector. By partially, the GDP of UMKM and minimum wage national average have asignificant effect, and investment of UMKM has no significant impact on the absorption oflabor in the UMKM sector. The most dominant is the GDP of UMKM.